2019
DOI: 10.1016/j.childyouth.2019.104496
|View full text |Cite
|
Sign up to set email alerts
|

Native American children and school readiness: A nationally representative study of individual and cumulative risks

Abstract: Using a nationally representative dataset (Early Childhood Longitudinal Study-Birth Cohort) and bioecological-cumulative disadvantage framework, the present study examined school readiness among American Indian and Alaska Native (AIAN) children. It investigated the relations between salient child and family risk experiences (i.e., poverty, preterm/low birth weight, low maternal education, single motherhood, inadequate prenatal care, teen motherhood, and severe maternal depression), and kindergarten academic (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 193 publications
0
11
0
Order By: Relevance
“…24 In 3 studies, parents self-identified as Indigenous. [40][41][42] In 2 studies, participants were recruited from health services that specifically provided care to Indigenous groups. 43,44 In the remaining 2 studies, parental Indigeneity was determined through offspring self-identification.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…24 In 3 studies, parents self-identified as Indigenous. [40][41][42] In 2 studies, participants were recruited from health services that specifically provided care to Indigenous groups. 43,44 In the remaining 2 studies, parental Indigeneity was determined through offspring self-identification.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Seven studies were conducted in the United States, 32,[34][35][36][37][38]42 and 2 each in Taiwan, 33,45 New Zealand, 40,41 and Australia. 43,44 One included Indigenous groups from Canada and the United States.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations